Determination of Location and Size of Circular Cavity Using Nonlinear Programming Techniques - Neny Kurniasih; Naoshi Nishimura; Shoichi Kobayashi (Institut Teknologi Bandung, 2001)
The applicability of the boundary integral equation method (BIEM) to the inverse elastodynamic problem is demonstrated. Once the forward problem is solved, the inverse one can be applied to determine some unknown physical parameters considered in the problem by minimization of the objective function in the least square sense. The size and location of circular cavity, as the unknown parameters, in a semi-infinite medium are determined, by providing the total displacement on the certain boundaries. The data of the total displacement may be obtained synthetically from the numerical analysis or observed from the experiment. Various nonlinear optimization techniques are used to determine the unknown parameters. The results have different convergence properties in achieving the optimum solution.